Thalidomide versus dexamethasone for the treatment of relapsed and/or refractory multiple myeloma: results from OPTIMUM, a randomized trial - Kropff, Martin; Hillengaß, Jens; Möhler, Thomas (Haematologica, the hematology journal, 2012)
Background: Thalidomide has potent antimyeloma activity, but no prospective, randomized controlled trial has evaluated thalidomide monotherapy in patients with relapsed/refractory multiple myeloma. Design and Methods: We conducted an international, randomized, open-label, four-arm, phase III trial to compare three different doses of thalidomide (100, 200, or 400 mg/day) with standard dexamethasone in patients who had received one to three prior therapies. The primary end-point was time to progression. Results: In the intent-to-treat population (N=499), the median time to progression was 6.1, 7.0, 7.6, and 9.1 months in patients treated with dexamethasone, and thalidomide 100, 200, and 400 mg/day, respectively; the difference between treatment groups was not statistically significant. In the per-protocol population (n=465), the median time to progression was 6.0, 7.0, 8.0, and 9.1 months, respectively. In patients who had received two or three prior therapies, thalidomide significantly prolonged the time to progression at all dose levels compared to the result achieved with dexamethasone. Response rates and median survival were similar in all treatment groups, but the median duration of response was significantly longer in all thalidomide groups than in the dexamethasone group. Adverse events reported in the thalidomide groups, such as fatigue, constipation and neuropathy, confirmed the known safety profile of thalidomide. Conclusions: Although thalidomide was not superior to dexamethasone in this randomized trial, thalidomide monotherapy may be considered an effective salvage therapy option for patients with relapsed/refractory multiple myeloma, particularly those with a good prognosis and those who have received two or three prior therapies. The recommended starting dose of thalidomide monotherapy is 400 mg/day, which can be rapidly reduced for patients who do not tolerate this treatment. (Clinical trial registration number: NCT00452569)
Gesehen am 26.07.2017